Simulation-Based Investigation of Wind Turbine Induced Shadow Flicker on IGBT Reliability and Energy Yield in Solar Converters in Hybrid Wind-Solar Systems - Leander Van Cappellen; Martijn Deckers; Kristof Engelen; Georgi H. Yordanov; Michael Daenen (IEEE Access)
With the growing adoption of renewable energy, hybrid wind-solar plants are gaining interest because they allow the increase of energy yield per unit of surface area. However, the presence of wind turbines creates unique shading scenarios for the solar panels. This work presents a simulation-based approach to investigate the solar plant’s energy yield and converter IGBT lifetime in the presence of dynamic and fast-moving shadows created by the wind turbine blades. First, the need for a dynamic simulation as opposed to a static one is examined. Next, the sensitivity of Photovoltaic (PV) string orientation, PV string location, wind direction, Maximum Power Point Tracker (MPPT) control speed, and turbine rotor speeds on energy yield and IGBT lifetime are investigated in a case study. Results show that dynamic and static simulations can show vastly different results. MPPT can have difficulty with shadow flicker, resulting in different string voltages depending on the MPPT update speed and wind turbine rotor speed. The shadow flicker introduces additional temperature swings in the IGBT, but these are too small to add any significant lifetime consumption (<1.2%). Thus, the observed changes in lifetime consumption are caused mainly by controller behavior and static shadows. Finally, it is concluded that PV strings are better placed south, east, or west of the wind turbine for optimal energy yield and lifetime consumption. A northern placement can be suitable if there is a significant distance (+50 m) between the PV string and the wind turbine.